2009
DOI: 10.1007/s11258-009-9629-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemistry of local vegetation gradients in sandy calcareous grasslands

Abstract: Acidification and N-deposition are continuous processes that alter the composition of plant communities. We investigated vegetation transitions in sandy grasslands and tested two hypotheses: (1) a shift from vegetation dominated by Koeleria glauca to one dominated by Corynephorus canescens is due to acidification and (2) a shift from vegetation dominated by K. glauca to one dominated by Arrhenatherum elatius is due to increased mineral-N. The occurrence of K. glauca and C. canescens followed pH shifts striking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…In another study of xeric sand calcareous grasslands in southern Sweden, a high N concentration was found to induce a shift from calcareous grassland vegetation towards vegetation dominated by the grass Arrhenatherum elatius (Mårtensson and Olsson 2010). When investigating the effect of nutrient addition on a nutrient-poor, calcareous inland sand ecosystem in Germany, Storm and Süss (2008) found that the above-ground production of vascular plants was doubled following N and NP treatments, and that the cover and/or height of nearly all the species investigated increased following high doses of N. P application alone had little effect, which may indicate that the system in question was N limited.…”
Section: Threats To Calcareous Grasslandsmentioning
confidence: 95%
See 2 more Smart Citations
“…In another study of xeric sand calcareous grasslands in southern Sweden, a high N concentration was found to induce a shift from calcareous grassland vegetation towards vegetation dominated by the grass Arrhenatherum elatius (Mårtensson and Olsson 2010). When investigating the effect of nutrient addition on a nutrient-poor, calcareous inland sand ecosystem in Germany, Storm and Süss (2008) found that the above-ground production of vascular plants was doubled following N and NP treatments, and that the cover and/or height of nearly all the species investigated increased following high doses of N. P application alone had little effect, which may indicate that the system in question was N limited.…”
Section: Threats To Calcareous Grasslandsmentioning
confidence: 95%
“…Olsson et al (2009) found a high number of red-listed plant species in nutrient-poor sandy grasslands, but the highest numbers were found on neutral to slightly alkaline soils, and a few species seemed to be restricted to alkaline soils. A later survey of the same grasslands revealed that decreasing pH brought about a shift from calcareous grassland vegetation towards heath vegetation dominated by Corynephorous canescens (Mårtensson and Olsson 2010). The grass heath (Natura 2000 code 2330) is also a protected vegetation type, but in Sweden this vegetation type is more abundant and has fewer red-listed species than xeric sand calcareous grassland (Olsson et al 2009).…”
Section: Threats To Calcareous Grasslandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest concentrations of extractable PO 4 -and N found in the deep perturbation plots were 1.69 lg/g soil and 0.11 lg/g soil respectively. The corresponding lowest concentrations of PO 4 -and N found in target plots in the study area were 0.73 lg/g soil and 0.20 lg/g soil respectively (Mårtensson and Olsson 2010), suggesting that the recolonization was not limited by the PO 4 -availability but could have been limited by the N availability. The most successful colonizer after both kinds of perturbation was C. canescens, covering over 35% of the perturbated plots and only 7% of the control plots.…”
Section: Effects Of Soil Perturbation On Vegetationmentioning
confidence: 87%
“…The Ellenberg index is, however, only valid under competition, and could change when competition is low. When studying pH gradients and vegetation on sandy soils in southern Sweden, Mårtensson and Olsson (2010) found that C. canescens occurred, and sometimes dominated, on soils with a high pH. Olsson et al (2009) found that C. canescens also occurred frequently in plots with a very high pH, and in particular in recently disturbed areas.…”
Section: Effects Of Soil Perturbation On Vegetationmentioning
confidence: 99%